Implementasi Pemberian Layanan Konseling Inividual Psikoanalisis Dalam Menangani Siswa Yang Mengalami Broken Home - Rahmawati, Feby; Krisnanda, Veno Dwi; Rufaidah, Anna (Universitas Indraprasta PGRI, 2023)
this study aims to determine the results of the implementation of individual psychoanalytic counseling services in dealing with students who experience Broken homes at SMPN 214 Jakarta. The research method used is qualitative research with a descriptive approach. There were six research informants, with three students as key informants, one guidance counselor as a key informant, and two homeroom teacher support informants from these students. Data collection tools through interviews, observation, and documentation. The results of the study show that the implementation of psychoanalytic individual counseling services is said to be successful in dealing with students who experience Broken homes. This conclusion is obtained based on data from counseling teachers who have implemented psychoanalytic individual counseling services for students who experience Broken homes. The use of psychoanalytic techniques in this service can make students reconcile with their past and experience positive change. Children who experience Broken homes really need special attention in overcoming developmental problems that are not appropriate for their age, caused by the main factor, namely an incomplete family.